The development of van hiele geometric thinking levels in a computer-supported collaborative learning environment - Özkan, Emre. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This mixed methods study investigated the use of a well-designed computer-supported collaborative learning environment, namely Virtual Math Teams, to develop Turkish middle school students’ van Hiele geometric thinking levels and attitudes towards mathematics and technology. The study also qualitatively looked into students’ Virtual Math Teams discourse to better understand factors leading to higher geometric thinking scores. The sample of the study consisted of 5th and 7th grade students who are at the visualization level according to the van Hiele geometric thinking test from a public and a private schools in İstanbul (n=24). For treatment, students are presented with instruction, which was developed based on Hiele’s phased-based instruction strategy, within the Virtual Math Teams environment on quadrilaterals (trapezoid, rhombus, parallelogram, rectangle, and square). The data were collected by using van Hiele geometric test and mathematics and technology scale for the quantitative part, and involved the Virtual Math Teams chat logs for qualitative part. The quantitative results showed a statistically significant development on the students’ van Hiele geometric thinking. Furthermore, the students’ attitudes towards mathematics and technology did not change except a subscale that is attitudes to learning mathematics with technology. There was a statistically significant increase in the students’ attitudes to learning mathematics with technology after the treatment. Qualitative results pointed out that collaboration among students could be an essential factor to develop students’ geometric thinking levels within the Virtual Math Teams environment.
Keywords: Geometry -- Study and teaching.; Van Hiele Model.; Educational technology.